PTSD and conflict behavior between veterans and their intimate partners - Miller, Mark W. (2013)
This study examined the influence of trauma history and PTSD symptoms on the behavior of veterans and their intimate partners (287 couples; N = 574) observed during conflict discussions and coded using the Rapid Marital Interaction Coding System (Heyman, 2004). Dyadic structural equation modeling analyses showed that PTSD was associated with more frequent displays of hostility and psychological abuse and fewer expressions of acceptance and humor in both veterans and their partners. Findings provide new insight into the social and emotional deficits associated with PTSD and emphasize the importance of addressing the trauma histories and PTSD of both partners when treating veteran couples with relationship disturbance.